PERTUNJUKAN WAYANG KULIT PURWA LAKON “CUPU MANIK ASTAGINA” SEBAGAI MEDIA DAKWA - Muh Mukti (Imaji, 2012)
This research tries to answer the following research questions: (1) how is the perfection of the purwa leather puppet performance entitled “Cupu Manik Astagina” as a sermon? (2) What lessons are taught? and (3) How are the lessons delivered through the leather puppet performance? This research is a descriptive-qualitative research. The data collecting technique was conducted through library research, observation and interview, and documentation. The research results show: (1) the perfection of the performance of purwa leather pupet entitled “Cupu Manik Astagina” as a sermon cannot be gained optimally as it only achieves the the targhiblevel, not the takhrujlevel. (2) The religious lessons given are those related to hablumminalllah (relationship with God), hablumminannaas(relationship among human beings), dan hablumminal ‘alm(relationship with nature). (3) The methods of delivering the religious lessons are methok, and medhang miring.